Optimization of condition of target irradiation for radionuclide production - Dovbnya, A.M.; Shramenko, B.I.; Torgovkin, A.V. (Вопросы атомной науки и техники, 2004)
In this report the different target arrangement relative to the bremsstrahlung beam have been considered. The analyses of spectral and angular distributions of bremstrahlung from different targets and as function of incident electron energy have been done. The worked out activity dependence on parameters of radionuclide target and bremstrahlung converter has been investigated. The different target arrangements relative to the bremsstrahlung beam have been considered. The analyses of spectral and angular distributions of bremstrahlung from different targets and as function of the incident electron energy have been done. The worked out activity dependence on parameters of a radionuclide target and a bremsstrahlung converter has been investigated. The recommendations concerning the optimal bremsstrahlung converter and target arrangement intention and the beam efficiency have been developed. Розглянуті різні варіанти розташування мішеней стосовно пучка гальмових фотонів. Проведено аналіз спектральних і кутових розподілів гальмових фотонів від різних гальмових мішеней і при різній енергії падаючих електронів. Досліджено залежність величини активності, що напрацьовується від параметрів радіонуклідної мішені і гальмового конвертора. У результаті досліджень дані рекомендації з вибору оптимального гальмового конвертора й оптимальної геометрії розташування мішеней у залежності від мети опромінення й обраного коефіцієнта використання пучка. Рассмотрены различные варианты расположения мишеней по отношению к пучку тормозных фотонов. Проведен анализ спектральных и угловых распределений тормозных фотонов от различных тормозных мишеней и при различной энергии падающих электронов. Исследована зависимость величины нарабатываемой активности от параметров радионуклидной мишени и тормозного конвертора. В результате исследований даны рекомендации по выбору оптимального тормозного конвертора и оптимальной геометрии расположения мишеней в зависимости от цели облучения и выбранного коэффициента использования пучка.